Կիլիկիայի Հայոց թագավոր Լեւոն Մեծագործի թագադրման հարցի շուրջ - Վահե Թորոսյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Третий Крестовый поход имел положительное влияние на армянское княжество Рубинянов. В 1190 - 1197 гг. в результате активных дипломатических переговоров Левону удалось получить согласие Генриха VI и Папы Римского на провозглашение княжества Рубинянов королевством. Как известно, корона была присвоена Левону императором Византии Алексеем III. The third Crusade had a positive influence upon the Armenian Rubenid Princedom. From 1190 to 1197 through active and measured diplomatic negotiations Levon managed to obtain consent by Henry VI and the Pope to assert the Rubenid Princedom as Kingdom. As it is known, Alexios III, the Emperor of Byzantium awarded a crown to Levon. Some researchers believe that despite accepting the crown sent by Alexios III.
Keywords: History; Medieval History